Mechanism of Immune System Dysfunction, Apoptosis and Oxidative Stress on Endometriosis - Miftahuz Zakiyah; Asmarinah Asmarinah (Faculty of Medicine, Universitas Diponegoro, 2023)
Endometriosis is gynecology disease that still needs advance knowledge to develop best treatment for enhancingÂ the best quality of patient life. It is characterized by forming the endometrium tissue outside the uterus and happened approximately in 5-10% of reproductive women. Endometriosis with poor prognosis can be a high risk of endometrium cancer, ovarian cancer and results in infertility. A deep attempt to reach the knowledge of clear molecular etiology of endometriosis is needed. Here, there are three molecular mechanism dysfunction that occurs on endometriosis; (1) immune system dysfunction, (2) disturbance in apoptosis signal, (3) and oxidative stress elevation. Therefore, the determination of molecular pathogenesis of endometriosis will be useful in developing of diagnostic and therapeutic methods.